Dualities in Shakespeare - Smith, Marion Bodwell, 1912- (Heritage., 1966)
This is a study of particular aspects of particular works in a particular context. The context, in general terms, is the humanist search for a synthesis or order based on the reconciliation of oppositions, for unity in difference, in spite of growing philosophical disillusionment and social disruption.